Food in the Making of Modern Korea - Lee, Cherl-Ho. author. aut Link
XIV, 399 p. 89 illus., 65 illus. in color.
Keywords: This handbook offers an updated and comprehensive presentation of knowledge on Korean modern and contemporary food history. It covers the changes in food availability, nutrition, and the health status of Koreans, and the Korean food industry's development from the late period of Joseon dynasty in the mid-19th century, to the present. This period includes the severe poverty and food shortage of the Joseon dynasty, followed by the Japanese invasion, Independence and the South-North division, the Korean war, and rapid industrial development. The influence of national and international environments and political changes during the last 150 years on the Korean food security and the nutritional situation of the people is demarcated. In doing so, the author makes novel suggestions on possible contributions to alleviate the world food crisis in the future. Relevant to food historians and food scientists, and East Asian studies scholars with a particular interest in Korean culture and history, this is a pioneering work that elucidates the driving forces for the development and betterment of Korean society—through food acquisition.